Nrf2 functions as a pyroptosis-related mediator in traumatic brain injury and is correlated with cytokines and disease severity: a bioinformatics analysis and retrospective clinical study - Zhao, Gengshui; Zhao, Jianfei; Lang, Jiadong; Sun, Guozhu (Frontiers in Neurology, 2024)
Background Traumatic brain injury (TBI) is a serious hazard to human health. Evidence has accumulated that pyroptosis plays an important role in brain trauma. The aim of this study is to screen potential key molecules between TBI and pyroptosis, and further explore their relationships with disease severity and cytokines. Methods To acquire differentially expressed genes (DEGs) before and after brain injury, the GSE89866 dataset was downloaded from the Gene Expression Omnibus (GEO) database. Meanwhile, pyroptosis-related genes were obtained from the GeneCards database, and the intersected genes were identified as differentially expressed pyroptosis-related genes (DEPGs). Moreover, the hub genes were screened via four algorithms (namely Maximum Clique Centrality, Edge Percolated Component, BottleNeck and EcCentricity) in Cytoscape software. Blood levels of Nrf2 were measured by ELISA using a commercially available kit. Finally, we further investigated the correlation between Nrf2 levels and medical indicators in TBI such as clinical characteristics, inflammatory cytokines, and severity. Results Altogether, we found 1,795 DEGs in GSE89866 and 98 pyroptosis-related genes in the GeneCards database. Subsequently, four hub genes were obtained, and NFE2L2 was adopted for further clinical study. By using Kruskal-Wallis test and Spearman correlation test, we found that the serum Nrf2 levels in severe TBI patients were negatively correlated with GCS scores. On the contrary, there was a positive correlation between serum Nrf2 levels and pupil parameters, Helsinki CT scores, IL-1 β and IL-18. Conclusions In summary, bioinformatic analyses showed NFE2L2 plays a significant role in the pathology of TBI. The clinical research indicated the increase in serum Nrf2 levels was closely related to the severity of trauma and cytokines. We speculate that serum Nrf2 may serve as a promising biochemical marker for the assessment of TBI in clinical practice.